2022
DOI: 10.3389/fimmu.2022.1033483
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of Toll-like receptors in lung cancer immunity and immunotherapy

Abstract: Lung cancer is currently the leading cause of cancer-related deaths worldwide. Significant improvements in lung cancer therapeutics have relied on a better understanding of lung cancer immunity and the development of novel immunotherapies, as best exemplified by the introduction of PD-1/PD-L1-based therapies. However, this improvement is limited to lung cancer patients who respond to anti-PD-1 immunotherapy. Further improvements in immunotherapy may benefit from a better understanding of innate immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 105 publications
0
17
0
Order By: Relevance
“…Previous studies have shown that the conformation of flexible loops is altered in mutated nsp1, leading to a loss of coronavirus nsp1 function 48,49 . To investigate which conserved amino acid is required for nsp1‐induced IFN inhibition, we constructed eight nsp1 mutants (nsp1‐G38A, nsp1‐F39A, nsp1‐F44A, nsp1‐V45A, nsp1‐G85A, nsp1‐G87A, nsp1‐N95A, and nsp1‐L98A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the conformation of flexible loops is altered in mutated nsp1, leading to a loss of coronavirus nsp1 function 48,49 . To investigate which conserved amino acid is required for nsp1‐induced IFN inhibition, we constructed eight nsp1 mutants (nsp1‐G38A, nsp1‐F39A, nsp1‐F44A, nsp1‐V45A, nsp1‐G85A, nsp1‐G87A, nsp1‐N95A, and nsp1‐L98A).…”
Section: Discussionmentioning
confidence: 99%
“…47 Our findings indicated that the nsp1 induced the degradation of Previous studies have shown that the conformation of flexible loops is altered in mutated nsp1, leading to a loss of coronavirus nsp1 function. 48,49 To investigate which conserved amino acid is required for nsp1-induced IFN inhibition, we constructed eight nsp1 mutants (nsp1-G38A, nsp1-F39A, nsp1-F44A, nsp1-V45A, nsp1-G85A, nsp1-G87A, nsp1-N95A, and nsp1-L98A). We found that mutation of the conserved amino acids abolished the inhibiting IFN production activity of nsp1.…”
Section: We Found That Nsp1 Exhibited Ifn Antagonist Properties By In...mentioning
confidence: 99%
“…With advanced omics data analysis of lung cancer patients, numerous genetic and molecular studies have been reported for pathophysiological characterization of lung cancer progression and the development of target-therapeutics [3][4][5]. Recently, the development of therapeutic targets focusing on toll-like receptors (TLRs) and epidermal growth factor receptor (EGFR) signaling is being potentially considered in lung cancers [6][7][8][9]. TLRs have been identified on tumor cells, where their activation may orchestrate downstream signaling pathways that serve crucial functions in tumorigenesis and tumor progression [6,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development of therapeutic targets focusing on toll-like receptors (TLRs) and epidermal growth factor receptor (EGFR) signaling is being potentially considered in lung cancers [6][7][8][9]. TLRs have been identified on tumor cells, where their activation may orchestrate downstream signaling pathways that serve crucial functions in tumorigenesis and tumor progression [6,7,10]. In addition, TLRs play an essential role in lung cancer progression including cell growth, invasion, and angiogenesis [10].…”
Section: Introductionmentioning
confidence: 99%
“…After recognizing and binding to their respective ligands, they recruit adaptor molecules and initiate downstream signaling pathways such as cell activation and transcription of inflammatory genes (8). PAMPs can be expressed by pathogens or invasive microbes, whereas DAMPs are stress signals released or exposed on the membrane of damaged cells and include components that are normally found intracellularly, such as adenosine triphosphate, calreticulin, annexin A1, high mobility group box 1 (HMGB1), heat shock (HSP), and S100 proteins (9). Dr. William Coley, acknowledged as the forefather of cancer immune therapy, provided in 1891 the first evidence that bacterial immune toxins could reactivate the host immune system to fight tumor progression in inoperable cancer patients, without knowing either the mechanism of action of those PAMPs or the target receptors and immune cells (10).…”
Section: Introductionmentioning
confidence: 99%